Contradictions in Indonesia's Legal Approach To Abortion: A Study of Reproductive Health Law and The Criminal Code - I Made Suryana; Putu Ayu Sani Utami (Eduvest - Journal of Universal Studies, 2024)
This research examines the legal approach to abortion in Indonesia, focusing on the significant conflict between the Indonesian Criminal Code's provisions on abortion and the stance of the Reproductive Health Law. The study aims to understand the implications of this legal contradiction on women's reproductive health and rights, and propose potential solutions to harmonize the legal framework. It employs a comparative legal analysis method, investigating the origins, interpretations, and effects of the respective laws, with data collected from legal documents, scholarly articles, and databases. The findings reveal that the existing legal contradiction potentially contributes to unsafe abortion practices, leading to adverse health consequences and undermining women's rights. The study proposes amendments to align the Criminal Code with the Reproductive Health Law, policy reforms, and cultural initiatives based on international best practices and scholarly recommendations. The research emphasizes the need for comprehensive reproductive health services that respect women's rights and protect their health, thereby advocating for a safer and more inclusive environment in Indonesia.